1966
DOI: 10.1037/h0023712
|View full text |Cite
|
Sign up to set email alerts
|

Self concept reports among hospitalized alcoholics during early periods of sobriety.

Abstract: Self-concept reports of 35 hospitalized male alcoholics, as measured by the McKmney Sentence Completion Blank, were examined for relationships with the sobriety interval in the hospital setting. A negative relationship (r-.33) was noted between the length of time sober and the index of a favorable concept of self, and a positive correlation (r = .24) resulted from measures of the sobriety interval and responses indicating self defeat, guilt and fear. Mechanisms of these relationships were discussed in the fram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1969
1969
1980
1980

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…For example, Chodorkoff (1964) claimed that alcoholics need to support their deficient ego through physiological changes rendered by alcoholic intoxication. In a similar vein, White and Porter (1966) reported that self-concepts of hospitalized alcoholics become less favorable as the duration of abstinence increases. Furthermore, Hurvitz and Lelos (1968) concluded that alcoholics have a conflicting selfimage, presenting a dominant facade yet yearning for a dependent role.…”
mentioning
confidence: 86%
“…For example, Chodorkoff (1964) claimed that alcoholics need to support their deficient ego through physiological changes rendered by alcoholic intoxication. In a similar vein, White and Porter (1966) reported that self-concepts of hospitalized alcoholics become less favorable as the duration of abstinence increases. Furthermore, Hurvitz and Lelos (1968) concluded that alcoholics have a conflicting selfimage, presenting a dominant facade yet yearning for a dependent role.…”
mentioning
confidence: 86%